2016
DOI: 10.1089/jwh.2015.5416
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Function and Quality of Life in Women Treated for Stress Urinary Incontinence: Tension-Free Transobturator Suburethral Tape Versus Single-Incision Sling

Abstract: In our study, both slings showed a high rate of continence without any major complications. The sexual function also improved sharply in all the six FSFI domains, with no statistically significant difference between the two treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…After 12 months of follow-up, the FSFI total score in the SIS group improved from baseline 22.7 ± 3.8 to 26.2 ± 4.0. Similarly, Pastore et al [41] in their prospective randomized study evaluating the effect of tension-free TOT versus single-incision sling found improvement in sexual functions in all the 6 FSFI domains, with no statistically significant difference between the 2 treatment groups. Further studies are needed to evaluate the effects of various sling operations on sexual functions.…”
Section: Discussionmentioning
confidence: 79%
“…After 12 months of follow-up, the FSFI total score in the SIS group improved from baseline 22.7 ± 3.8 to 26.2 ± 4.0. Similarly, Pastore et al [41] in their prospective randomized study evaluating the effect of tension-free TOT versus single-incision sling found improvement in sexual functions in all the 6 FSFI domains, with no statistically significant difference between the 2 treatment groups. Further studies are needed to evaluate the effects of various sling operations on sexual functions.…”
Section: Discussionmentioning
confidence: 79%
“…Pastore et al used FSFI questionnaire to evaluate sexual function in 48 women who underwent TVT-O and SIS procedures. The postoperative FSFI scores were reported to improve significantly (p<0.001) in both groups, with high rate of continence ( 15 ). Naumann et al assessed sexual function six months after TVT and SIS surgeries and reported that, in comparison to preoperative scores, all postoperative domain scores and total FSFI score increased significantly in both surgical groups ( 16 ).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the social QoL of women is negatively affected. Despite the high prevalence and negative impact on life, very few women affected by UI seek treatment (28). In developing countries, the frequency of unspoken UI is high.…”
Section: Discussionmentioning
confidence: 99%